Kandungan Fitokimia dan Uji Toksisitas Jamu Susut Perut - Albert Jackson Yang; Fri Rahmawati; John Jackson Yang (Pro-Life, 2025)
Jamu Susut Perut is a traditional Indonesian herbal preparation widely used as a complementary therapy to support weight loss and reduce abdominal fat. It commonly contains medicinal plants such as Guazuma ulmifolia (Jati belanda), Curcuma longa (Turmeric), Zingiber purpureum (Bangle), Murraya paniculata (Kemuning), Orthosiphon aristatus (Cat’s whiskers), Gallae (Majakanis), Areca catechu (Betel nut), and Piperis folium (Betel leaf). These plants are rich in bioactive compounds including flavonoids, polyphenols, alkaloids, and saponins, which possess lipolytic, anti-inflammatory, and hepatoprotective properties that may enhance fat metabolism and lower blood lipid levels. This study aims to identify the phytochemical compounds in Jamu Susut Perut (X) using the Harborne method and to determine its toxicity against shrimp larvae (Artemia salina Leach) through the Brine Shrimp Lethality Test (BSLT). The LC₅₀ (lethal concentration 50%) value was calculated using probit analysis in SPSS and Microsoft Excel. The phytochemical screening revealed the presence of triterpenoids, quinones, flavonoids, and saponins in the herbal formulation. The toxicity test showed that Jamu Susut Perut (X) had an LC₅₀ value of 547.92 ppm, indicating toxicity to shrimp larvae since the value is below 1000 ppm. In conclusion, Jamu Susut Perut (X) contains bioactive compounds with potential pharmacological effects but also exhibits toxic properties at certain concentrations. This research provides scientific data to ensure the safe use of Jamu Susut Perut as a traditional herbal medicine for consumers.